THE ROLE OF SOCIOLINGUISTIC COMPETENCE IN SHAPING EFL LEARNERS’ COMMUNICATIVE ENGAGEMENT - Burhanuddin, Wildhan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
This study investigates the relationship between sociolinguistic competence and communicative engagement among Indonesian EFL learners. Using a mixed-methods design, the research combined quantitative analysis of scenario-based questionnaire responses with interpretive commentary of learners’ written answers. Descriptive results showed that students demonstrated strong pragmatic awareness in authority-related contexts but more variability in informal and ambiguous situations. Reliability analysis indicated that sociolinguistic competence is multidimensional rather than uniform. Inferential statistics revealed a moderate positive correlation between sociolinguistic competence and communicative engagement, while qualitative analysis highlighted the influence of cultural scripts of deference, harmony, and accountability on learners’ communicative choices. These findings underscore that willingness to communicate is not determined solely by linguistic ability but is shaped by sociocultural orientations and identity negotiations. Pedagogically, the study calls for greater integration of pragmatic and sociolinguistic instruction in EFL classrooms, emphasizing both authority-based and peer-oriented interactions. The study concludes that fostering pragmatic awareness within cultural contexts can enhance learners’ confidence and participation, supporting their development as contextually responsive communicators.